THE INFLUENCE OF LEADERSHIP, MOTIVATION, AND WORK DISCIPLINE ON PERFORMANCE EMPLOYEES AT THE DIRECTORATE OF VOCATIONAL HIGH SCHOOLS OF THE MINISTRY OFFICE EDUCATION AND CULTURE - Djasda, Djasda; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
The development of science and technology which is marked by advances in the field of information media and technology at this time has been going so rapidly, that in placing a nation in a position to the extent that the nation is advanced is based on how far the nation masters these two fields. The Indonesian nation is one of the nations that lives in a global environment, so inevitably it must also be involved in the back and forth of mastery of information and technology media, especially for the benefit of the nation itself. Human beings are the most important source that plays a role in determining the continuity and success in an organization, this is because no matter how perfect the technology is but can run well, therefore it is necessary to develop the human resource aspect. One of the aspects that plays an important role in a government bureaucracy is leadership. In addition, providing motivation is very important in being loyal